Bell-shaped porous metal structure and its manufacturing method
By thermoforming the bell structure of porous metal structure, the composite of the material and metal powder of inorganic particles and shells are used to form the material and the metal powder, the problems of material selection and shell size control in the prior art are solved, and high-performance sound absorption and vibration impedance effects are achieved.
Patent Information
- Application Number
- JP2023502554
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2022-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-02-25
AI Technical Summary
The prior art When manufacturing porous metal structures with bell structures, it is difficult to control the size and material selection of the shell, and the residual shell forming material will affect performance.
By obtaining a first composite containing inorganic particles and a shell forming material and forming a second composite with a metal powder, thermoforming is performed to form a bell structure of a porous metal structure. Different shell forming materials and inorganic particles can be selected and their proportions can be adjusted to optimize sound absorption and vibration impedance properties.
This method simplifies the manufacturing process, reduces the residue of shell-forming materials, and enables the use of a variety of materials to achieve high sound absorption and vibration impedance performance, even exceeding the performance of vibration impedance rubber.
Smart Images

Figure 0007650536000001 
Figure 0007650536000002 
Figure 0007650536000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a porous metal structure having a bell structure and a method for manufacturing the same. [Background technology]
[0002] Conventionally, porous metal structures having a bell structure are known. The bell structure is a structure resembling a traditional Japanese bell, i.e., a structure in which movable particles exist inside a shell or in a hollow space, and it is also known that porous metal structures having such a structure have higher sound absorption and vibration damping properties than porous metal structures not having a bell structure.
[0003] Patent Documents 1 and 2 disclose a porous metal structure having such a bell structure and a method for producing the same. In both Patent Documents 1 and 2, the bell structure is formed by coating the inner particles of the bell structure with hollow silica particles, which are then sintered together with metal powder that is the base material of the porous metal structure. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-5459 A [Patent Document 2] JP 2020-70482 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present disclosure provides a novel porous metal structure having a bell structure and a method for producing the same. [Means for solving the problem]
[0006] The present inventors have found that the above problems can be solved by the present disclosure having the following aspects. Aspect 1 Obtaining a first composite of inorganic particles and a shell-forming material; obtaining a second composite of the first composite and a metal powder; heating the second composite to sinter the metal powder; and Removing the shell-forming material from the second composite body and forming a bell structure with the sintered metal powder as a shell and the inorganic particles as internal particles, or forming a bell structure with the shell-forming material as a shell and the inorganic particles as internal particles. A method for producing a porous metal structure having a bell structure, comprising: Aspect 2 The method according to aspect 1, further comprising adding a binder for binding the inorganic particles and the shell-forming material when obtaining the first composite. Aspect 3 3. The method of claim 1 or 2, wherein the shell-forming material comprises activated carbon. Aspect 4 A method according to any one of aspects 1 to 3, wherein the shell-forming material is a carbon-based shell-forming material, and the second composite is heated in an oxygen-containing atmosphere to remove the carbon-based shell-forming material from the second composite. Aspect 5 2. The method according to claim 1, wherein the shell-forming material is an inorganic material, and the shell-forming material itself is used as the shell. Aspect 6 6. The method according to claim 5, wherein the shell-forming material is cylindrical. Aspect 7 The inorganic particles have a density of 7.0 g / cm 3 The method according to any one of aspects 1 to 6, wherein the metal powder is an aluminum-based metal powder, a tin-based metal powder, or a combination thereof. Aspect 8 The method according to any one of aspects 1 to 7, wherein the first composite is enveloped by the metal powder to obtain a second composite, thereby obtaining the porous metal structure in the form of particles. Aspect 9: Obtaining a plurality of porous metal structures having a bell structure by the manufacturing method according to any one of aspects 1 to 8; and impregnating the plurality of porous metal structures with molten metal and cooling; A method for producing a metal structure having a bell structure, comprising: Aspect 10 A porous metal structure having a bell structure in which movable inorganic particles are present in a shell, the inorganic particles having an average particle size of 100 μm or more and 5000 μm or less, and the shell having an average diameter in the range of 1.5 times or more and 10.0 times or less the average particle size of the inorganic particles. Aspect 11 11. The porous metal structure having a bell structure according to claim 10, wherein the shell is cylindrical. Aspect 12 12. The porous metal structure of claim 10 or 11, wherein the porous metal structure comprises tin. Aspect 13 13. The porous metal structure according to any one of embodiments 10 to 12, which is in the form of particles. Aspect 14 A metal structure comprising the porous metal structure according to any one of aspects 10 to 13 inside a solid metal portion. Aspect 15 15. The metal structure according to embodiment 14, having an island-in-a-sea structure, comprising the porous metal structure as a plurality of domain portions and the solid metal portion as a matrix portion. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 shows a schematic diagram and experimental results of how internal particles move when a structure having a bell structure is subjected to vibration. [Diagram 2] FIG. 2 shows a schematic diagram of one embodiment of a manufacturing process for a porous metal structure having a bell structure. [Diagram 3] FIG. 3 shows SEM photographs of the porous metal structures of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 produced in the examples. [Figure 4]FIG. 4 shows a schematic diagram of a measuring device for evaluating vibration damping performance used in the examples. [Diagram 5] FIG. 5 shows the evaluation results of the vibration damping performance measured for Example 1 and Comparative Examples 1 to 4. [Figure 6] FIG. 6 shows the evaluation results of vibration damping performance measured in an experiment in which the internal particles of the bell structure were changed. [Figure 7] FIG. 7 shows the evaluation results of vibration damping performance measured in experiments in which the amount of bell structure was changed. [Figure 8] FIG. 8 shows a schematic diagram of one embodiment of a manufacturing process for a metal structure having a bell structure. [Figure 9] Fig. 9(a) shows a schematic diagram of a second composite from which the carbon-based shell-forming material and other components have not been removed to obtain a particulate porous metal structure. Fig. 9(b) shows a schematic diagram of a particulate porous metal structure obtained by removing the carbon-based shell-forming material and other components from the second composite shown in Fig. 9(a). [Figure 10] FIG. 10 shows an external view and a cross-sectional photograph taken by an optical microscope of the porous metal structure having spherical particle form obtained in the example. [Figure 11] FIG. 11 shows a cross-sectional photograph taken by an optical microscope and an enlarged cross-sectional photograph taken by an SEM of the metal structure having a bell structure obtained in the example. [Figure 12] FIG. 12 shows a schematic process for obtaining a first composite body in the case where the shell-forming material itself becomes the shell. [Figure 13] FIG. 13 shows a cross-sectional view of a bell structure when manufactured by the process shown in FIG. [Figure 14] FIG. 14 shows the evaluation results of vibration damping performance measured for a bell structure in which the shell-forming material itself becomes the shell. [Figure 15] FIG. 15 shows the relationship between the Brinell hardness (HBW) of the porous metal and the mass ratio of the Sn powder to the total metal powder. [Figure 16] FIG. 16 shows the evaluation results of the vibration damping performance when Sn powder is used as the metal powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] <<Method for manufacturing a porous metal structure having a bell structure>> The method for producing a porous metal structure of the present disclosure includes obtaining a first composite containing at least inorganic particles and a shell-forming material; obtaining a second composite containing at least the first composite and a metal powder; sintering the second composite; and removing the shell-forming material from the second composite. By removing the shell-forming material from the second composite, a bell structure is formed in which the sintered metal powder becomes a shell and the inorganic particles become the internal particles. In addition, the method for producing a porous metal structure of the present disclosure may form a bell structure in which the shell-forming material itself is the shell and the inorganic particles become the internal particles, instead of removing the shell-forming material.
[0009] In the porous metal structure having a bell structure manufactured by the conventional technology such as Patent Documents 1 and 2, hollow silica particles and their residues remain inside the bell shell. In addition, in the conventional technology, it is difficult to control the size of the shell, and the manufacturing process is complicated. Furthermore, in the conventional technology, there is a limit to the selection of materials, and only specific materials are used for manufacturing. In contrast, it has been found that the manufacturing method disclosed herein can simplify the manufacturing process, reduce the residue of the shell-forming material in the final porous metal structure, and can be constructed from a wide variety of materials.
[0010] Furthermore, the manufacturing method of the present disclosure allows the preparation of porous metal structures having internal particles and shells of various sizes and materials, which allows the bell structure to be highly engineered to provide the porous metal structure with high sound absorption and / or vibration damping properties, which can be optimized according to the magnitude and frequency of the vibration to be absorbed.
[0011] And, it has been surprisingly found that the bell-shaped porous metal structure obtained in this way can, in some cases, achieve extremely high sound absorption and / or vibration damping properties on the same level as vibration-damping rubber.
[0012] <Step of Obtaining the First Composite> The manufacturing method of the present disclosure includes a step of obtaining a first composite containing at least inorganic particles and a shell-forming material. The inorganic particles constitute the movable internal particles of the bell-structured porous metal structure that is finally obtained. The shell-forming material forms the shell of the bell structure in the finally obtained porous metal structure with a bell structure. That is, the shell-forming material is finally removed to form a space that becomes the shell in the porous metal, or remains in the porous metal structure and becomes the shell as it is.
[0013] When the shell-forming material is finally removed, the first composite is preferably in a form in which the shell-forming material is attached to the inorganic particles, and particularly preferably in a form in which the shell-forming material is attached to substantially the entire surface of the inorganic particles. When only one bell-structured internal particle is desired, the first composite can be manufactured so as to contain only one inorganic particle, and when multiple bell-structured internal particles are desired, the first composite can be manufactured so as to contain multiple inorganic particles.
[0014] In this case, the method of compounding the inorganic particles and the shell-forming material may be simply mixing. For example, the method is not particularly limited, and may be wet mixing using a liquid medium or dry mixing. For mixing, a normal mixer, a Henschel mixer, an ultrasonic dispersion device, a homomixer, a mortar, a ball mill, a planetary stirrer, etc. may be used, but is not limited to these. The mixing time is also not particularly limited as long as it is possible to form a first complex that is sufficient for carrying out the method of the present disclosure.
[0015] When the shell-forming material remains in the porous metal structure and becomes the shell as it is, the shell-forming material is not particularly limited as long as it can contain inorganic particles inside and can continue to be a shell even after the process of sintering the metal powder. Therefore, in this case, the shell-forming material can be a hollow structure capable of containing inorganic particles inside, and the shell-forming material can be composed of, for example, an inorganic material, specifically, it can be composed of a material that can be used as the material of the inorganic particles described below. The shape of the hollow structure is not particularly limited, and it may be a spherical hollow structure, but is preferably cylindrical, and particularly cylindrical shapes such as a cylinder or a prism can be mentioned.
[0016] The inventors have found that extremely high sound absorption and / or vibration damping properties can be obtained by aligning the direction of the long axis of the cylindrical shell-forming material with the direction in which the porous metal structure receives vibration. When the cylindrical shell-forming material is used as the shell itself, the direction of the shell-forming material can be set relatively arbitrarily, so that the long axis of the shell-forming material can be approximately parallel to the direction in which the porous metal structure receives vibration. Preferably, the axis in the direction in which the porous metal structure is most susceptible to vibration and the long axis of the cylindrical shell-forming material are at an average angle of 40° or less, 30° or less, 20° or less, 15° or less, 10° or less, or 5° or less.
[0017] The inorganic particles can be, but are not limited to, particles of a material selected from the group consisting of metals, metalloids, and combinations thereof, as well as their oxides, nitrides, carbides, and borides, or composite materials thereof.For example, the inorganic particles can be particles containing or consisting of a material selected from the group consisting of silicon, aluminum, titanium, zirconium, zinc, iron, copper, nickel, lead, tungsten, and alloys containing them, as well as compounds thereof (particularly oxides, nitrides, carbides, and borides), or composite materials thereof.
[0018] Inorganic particles: 3.0 g / cm 3 More than 4.0g / cm 3 More than 5.0g / cm 3 More than 6.0g / cm3 More than 7.0g / cm 3 or more than 8.0g / cm 3 It may be made of a material having a specific gravity of 15.0 g / cm or more. 3 Below, 12.0g / cm 3 Below, 10.0g / cm 3 Below, 9.0g / cm 3 or less than 8.0g / cm 3 It may be made of the following materials: For example, inorganic particles with a density of 3.0 g / cm 3 More than 15.0g / cm 3 or less than 7.0g / cm 3 More than 12.0g / cm 3 It may be constructed from materials having the following specific gravities:
[0019] Among these, the present inventors particularly preferred 6.0 g / cm 3 or more than 7.0g / cm 3 It has been found that when heavy inorganic particles having a high specific gravity as described above are used, a bell-shaped porous metal structure having very high sound absorption and / or vibration damping properties can be obtained. Examples of such inorganic particles include iron, copper, tungsten, alloys thereof, and compounds thereof.
[0020] The shape of the inorganic particles is not particularly limited, but it is preferable that the inorganic particles have a shape that allows them to rub or collide with the shell wall surface inside the shell. For example, the inorganic particles may be any of the following shapes: amorphous; spherical, e.g., spherical ellipsoid; flaky, hexagonal plate, etc.
[0021] The present inventors have found that when inorganic particles move within a shell, friction between the shell and the inorganic particles is much greater when the inorganic particles slide within the shell than when the inorganic particles roll and contact the shell. Specifically, when inorganic particles slide within the shell, friction that is 100 to 1000 times greater than when the inorganic particles roll and contact the shell is generated. Therefore, the inventors have found that by designing the shape of the shell and the shape of the inorganic particles so that the inorganic particles slide within the shell, the porous metal structure can be given extremely high sound absorption and / or vibration damping properties.
[0022] From this viewpoint, when the shell-forming material remains within the porous metal structure and becomes the shell as it is, it is preferable that the inorganic particles are not spherical, but rather have a shape with a long axis such as a cylinder or rectangular prism so that they do not roll within the cylinder.
[0023] In this case, if the diameter of the cylindrical shell-forming material is sufficiently larger than the length of the long axis of the inorganic particles, the inorganic particles will rotate inside the shell regardless of their shape, so it is preferable to make the diameter of the cylindrical shell-forming material and the diameter of the short axis of the inorganic particles closer to each other to some extent. The average equivalent diameter of the inner diameter of the cylindrical shell-forming material may be 1.1 times, 1.2 times, 1.5 times, or 2.0 times or more, or 4.0 times or less, 3.0 times or less, or 2.0 times or less, or 1.1 times or more and 4.0 times or less, or 1.2 times or more and 2.0 times or less, of the average equivalent diameter of the short axis of the inorganic particles. The equivalent diameter refers to the diameter of a perfect circle having a perimeter length equal to the perimeter length of the surface. The average equivalent diameter of the short axis refers to the average equivalent diameter of the surface obtained when cut perpendicular to the long axis.
[0024] When the inorganic particles are large relative to the length of the major axis of the cylindrical shell-forming material, the movement distance of the inorganic particles in the cylinder is shortened, and the friction of the inorganic particles in the cylinder is reduced. Therefore, it is preferable to set the length of the major axis of the cylinder and the size of the inorganic particles so that the inorganic particles generate large friction in the cylinder. For example, the ratio of the diameter of the inorganic particles (particularly, the length of the major axis of the inorganic particles) to the length of the major axis of the cylinder (diameter of the inorganic particles / length of the major axis of the cylinder) can be 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, and may be 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less. For example, this ratio may be 0.1 or more and 0.9 or less, or 0.2 or more and 0.6 or less.
[0025] The average length of the major axis of the cylindrical shell-forming material may be 1 mm or more, 2 mm or more, 3 mm or more, 5 mm or more, or 10 mm or more, or 50 mm or less, 30 mm or less, 10 mm or less, 5 mm or less, or 3 mm or less. For example, the major axis of the cylindrical shell-forming material may be 1 mm or more and 50 mm or less, or 2 mm or more and 10 mm or less.
[0026] The average equivalent diameter of the minor axis of the cylindrical shell-forming material may be 0.1 mm or more, 0.5 mm or more, 1.0 mm or more, 3 mm or more, or 5 mm or more, or 10 mm or less, 5 mm or less, 3 mm or less, 1 mm or less, or 0.5 mm or less. For example, the major axis of the cylindrical shell-forming material may be 0.1 mm or more and 10 mm or less, or 0.5 mm or more and 3 mm or less.
[0027] The average particle size of the inorganic particles may be 10 μm or more, 50 μm or more, 100 μm or more, or 300 μm or more, and may be 5000 μm or less, 3000 μm or less, 2000 μm or less, 1500 μm or less, 1000 μm or less, 800 μm or less, or 500 μm or less. For example, the average particle size of the inorganic particles may be 10 μm or more and 5000 μm or less, 50 μm or more and 2000 μm or less, or 100 μm or more and 1000 μm or less. In this specification, the average particle size means the particle size at 50% of the cumulative value in the particle size distribution based on the number of particles selected at random and measured along the major axis of up to 100 particles using an optical electron microscope (or a vernier caliper if the diameter is large).
[0028] The inorganic particles may be 1% by mass or more, 2% by mass or more, 3% by mass or more, 5% by mass or more, or 7% by mass or more, or 30% by mass or less, 20% by mass or less, 15% by mass or less, or 10% by mass or less, based on the total mass of the finally obtained porous metal structure. For example, the inorganic particles may be 1% by mass or more and 30% by mass or less, or 2% by mass or more and 15% by mass or less, based on the total mass of the finally obtained porous metal structure.
[0029] In the case where the shell-forming material is finally removed, the shell-forming material is not particularly limited as long as it can be removed from the second composite and can form a shell in the finally obtained bell-shaped porous metal structure. Examples of the shell-forming material include carbon-based shell-forming materials and liquid-soluble shell-forming materials.
[0030] The present inventors have found that the finally obtained metal structure is a porous body, and thus the shell-forming material can be eliminated through the continuous pores. That is, by heating the second composite containing the carbon-based shell-forming material in an oxygen-containing atmosphere, the carbon of the carbon-based shell-forming material reacts with oxygen through the continuous pores of the porous body derived from the metal powder of the second composite to become carbon dioxide, even during or after the sintering of the metal powder of the second composite, and the carbon-based shell-forming material can be eliminated from the second composite. In addition, by contacting the second composite containing the liquid-soluble shell-forming material with a liquid in which the shell-forming material dissolves, the liquid-soluble shell-forming material can be dissolved into the liquid through the continuous pores of the porous body derived from the metal powder of the second composite, and the liquid-soluble shell-forming material can be eliminated from the second composite.
[0031] The carbon-based shell-forming material is not particularly limited as long as it can be heated in an oxygen-containing atmosphere to cause most of the carbon-based shell-forming material to disappear, and can form a shell in the finally obtained porous metal structure having a bell structure. For example, the carbon-based shell-forming material can be a carbon-based material, such as activated carbon, graphite, graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), carbon fiber, carbon nanotube, graphene, carbon black, etc. These carbon-based shell-forming materials essentially made of carbon are preferable because they can be turned into carbon dioxide and disappeared by heating in an oxygen-containing atmosphere. In addition, the carbon-based shell-forming material may be a carbon-containing material such as various polymers and hydrocarbons.
[0032] The liquid-soluble shell-forming material is not particularly limited as long as it can dissolve the liquid-soluble shell-forming material into the liquid through the continuous pores of the porous body derived from the metal powder of the second composite, and can eliminate the liquid-soluble shell-forming material from the second composite. For example, the liquid-soluble shell-forming material may be soluble in an organic solvent or may be soluble in an aqueous solvent. For example, when the liquid-soluble shell-forming material is soluble in an aqueous solvent, water-soluble substances such as water-soluble inorganic compounds such as sodium chloride and calcium chloride, and water-soluble polymers such as polyethylene glycol can be mentioned, and when the liquid-soluble shell-forming material is soluble in an organic solvent, organic polymers such as acrylic resin can be mentioned. In particular, when the liquid-soluble shell-forming material is removed after sintering the metal powder, the liquid-soluble shell-forming material can be soluble in a liquid in a state after being heated to the sintering temperature of the metal powder or higher. In this case, even when a water-soluble polymer is used as the liquid-soluble shell-forming material, it may be carbonized when heated to the sintering temperature or higher, and can be removed with an organic solvent. For example, when a water-soluble inorganic compound such as sodium chloride is used as the liquid-soluble shell-forming material, the water-soluble inorganic compound usually does not change even when heated to above the sintering temperature of the metal powder, and is preferable because it can be removed by allowing water to penetrate through the air holes in the porous metal structure.
[0033] When the shell-forming material is finally removed, the ratio of the mass of the shell-forming material to the mass of the inorganic particles in the first composite (mass of shell-forming material / mass of inorganic particles) may be 0.01 or more, 0.05 or more, 0.1 or more, 0.2 or more, 0.3 or more, or 0.5 or more, and may be 2.0 or less, 1.0 or less, 0.5 or less, 0.3 or less, or 0.2 or less. For example, this mass ratio may be 0.01 or more and 2.0 or less, or 0.05 or more and 0.3 or less. By adjusting the amount of the shell-forming material in the first composite, the size of the bell-structured shell of the finally obtained porous metal structure can be adjusted.
[0034] The number of inorganic particles contained in the first composite may be one or two or more. When the first composite contains a plurality of inorganic particles, a plurality of movable inorganic particles are present in the bell-shaped shell. When the first composite contains a plurality of inorganic particles, the number of inorganic particles in each of the first composites used to manufacture the porous metal structure may be different.
[0035] In the case where the shell-forming material is finally removed, a binder may be further used to bind the inorganic particles and the shell-forming material when obtaining the first composite, if necessary. The type of binder is not particularly limited as long as it can provide a first composite having an appropriate size for binding the inorganic particles and the shell-forming material to form a bell structure, but for example, various polymers such as hydrocarbon substances such as paraffin and wax, olefin resins, acrylic resins, epoxy resins, urethane resins, phenolic resins, and styrene-butadiene rubber can be used as the binder. In addition, sugars (sucrose, starch, etc.), gelatin, polyethylene oxide, polypropylene oxide, polyvinyl alcohol, polyethylene glycol, etc. may also be used.
[0036] Furthermore, the form of the binder when the inorganic particles and the shell-forming material are composited or mixed is not particularly limited, but examples thereof include a fusible binder that is used in a molten form upon heating, a water-soluble binder that is dissolved in water and used, an organic solvent-soluble binder that is dissolved in an organic solvent and used, and an emulsion-based binder.
[0037] In the case where the shell-forming material is finally removed, a step of applying a coating material to the first composite may be performed after the step of obtaining the first composite in order to adjust the size of the bell structure finally obtained. The coating material is not particularly limited as long as it can coat the first composite and can be substantially removed when heated in an oxygen-containing atmosphere after being carbonized as necessary. For example, various polymers such as hydrocarbon-based substances such as paraffin and wax, olefin-based resins, acrylic resins, epoxy resins, urethane resins, phenolic resins, and styrene-butadiene rubber can be used as the coating material.
[0038] The method for applying the coating material is not particularly limited, and any known method for coating particles can be used. For example, the coating material may be dissolved in a solvent and spray-coated or dip-coated onto the first composite.
[0039] If the first composite comprises a binder and / or a coating material, the step of sintering the metal powder may include a step of carbonizing the binder and / or coating material, which carbonizes them so that they can subsequently be removed together with the shell-forming material, and which may be carried out at a sufficient temperature and for a sufficient time, and may be carried out under vacuum or inert atmosphere.
[0040] When the shell-forming material is finally removed, a step of classifying the first composite may be added after the step of obtaining the first composite in order to make the size of the bell structure finally obtained appropriate. The classification method is not particularly limited, and examples thereof include sieving using a mesh, centrifugation using a cyclone, etc.
[0041] When the shell-forming material is finally removed, the first composite can have an appropriate size to form a bell structure, and the average particle size of the first composite may be 1.5 times or more, 2.0 times or more, 3.0 times or more, 4.0 times or more, or 5.0 times or more, or 10.0 times or less, 8.0 times or less, 6.0 times or less, 5.0 times or less, or 3.0 times or less, of the average particle size of the inorganic particles. The average particle size of the first composite may be in the range of 1.5 times or more and 10.0 times or less, or 2.0 times or less and 5.0 times or less of the average particle size of the inorganic particles. In addition, the average particle size of the first composite refers to the average particle size after the above-mentioned coating material application process and classification process are performed, if there are any. When the average particle size of the first composite and the average particle size of the inorganic particles are in such a range, when vibration is applied to the finally obtained porous metal structure, the inorganic particles are likely to collide with the wall surface of the shell in the bell structure, and the vibration damping property is extremely high, which is preferable.
[0042] The average diameter of the first complex may be 50 μm or more, 100 μm or more, 300 μm or more, 500 μm or more, 700 μm or more, 1000 μm or more, or 1500 μm or more, or 10000 μm or less, 8000 μm or less, 5000 μm or less, 3000 μm or less, 2000 μm or less, 1500 μm or less, 1000 μm or less, 800 μm or less, or 500 μm or less. For example, the average particle size of the first complex may be 50 μm or more and 10000 μm or less, 300 μm or more and 3000 μm or less, or 500 μm or more and 1500 μm or less.
[0043] The volume fraction of the first composite relative to the finally obtained porous metal structure (first composite / porous metal structure) may be 0.5 volume% or more, 1.0 volume% or more, 2.0 volume% or more, 3.0 volume% or more, 5.0 volume% or more, 10.0 volume% or more, 15.0 volume% or more, or 20.0 volume% or more, or 30.0 volume% or less, 20.0 volume% or less, 15.0 volume% or less, 10.0 volume% or less, or 5.0 volume% or less, calculated from the total volume of the first composites actually used and the volume of the finally obtained porous metal structure. This volume fraction may be, for example, 5.0 volume% or more and 30.0 volume% or less, or 1.0 volume% or more and 15.0 volume% or less. The total volume of the first composite is determined from the average particle size of the first composite and the number of the first composites used.
[0044] In one embodiment, the average particle size of the inorganic particles is 100 μm or more and 5000 μm or less, and the average diameter of the first composite is in the range of 1.5 to 10.0 times the average particle size of the inorganic particles; the average particle size of the inorganic particles is 100 μm or more and 1000 μm or less, and the average diameter of the first composite is in the range of 2.0 to 5.0 times the average particle size of the inorganic particles.
[0045] <Step of Obtaining Second Complex> The manufacturing method of the present disclosure includes a step of obtaining a second composite containing at least the first composite obtained as described above and a metal powder, which constitutes a porous metal portion that becomes a base material in the finally obtained porous metal structure.
[0046] The second composite is preferably in a form in which the metal powder is attached to the first composite, and particularly preferably in a form in which the metal powder is attached to substantially the entire surface of the first composite. When only one bell structure is to be formed in the porous metal structure, the second composite can be manufactured so as to include only one first composite, and when multiple bell structures are to be formed in the porous metal structure, the second composite can be manufactured so as to include multiple first composites.
[0047] The method of compounding the first composite with the metal powder may be mixing and / or kneading, or the first composite may be simply wrapped with the metal powder or a slurry containing the metal powder without mixing. The method of mixing and / or kneading is not particularly limited, and may be wet mixing using a liquid medium or dry mixing. For mixing, a normal mixer, a Henschel mixer, an ultrasonic dispersion device, a homomixer, a mortar, a ball mill, a planetary stirrer, etc. may be used, but is not limited to these. The mixing time is also not particularly limited as long as a second composite that is sufficient for carrying out the method of the present disclosure can be formed.
[0048] The type of metal powder is not particularly limited as long as it can be sintered to form a porous metal portion. All types of metal powders that can form porous metal by powder metallurgy can be used, and examples of such metal powders include iron-based metals including stainless steel, copper-based metals, titanium-based metals, tungsten-based metals, aluminum-based metals, chromium-based metals, nickel-based metals, zinc-based metals, magnesium-based metals, tin-based metals, lead-based metals, and alloys of combinations thereof. In this specification, the term "based metal" refers to the metal alone or an alloy containing the metal as the main component.
[0049] It has been found that, among metal powders, particularly when soft metal powders are used as the metal material, extremely high sound absorption and / or vibration damping properties can be obtained. For example, when aluminum powder and tin powder are mixed with metal powder, the higher the mixing ratio of soft tin powder, the higher the sound absorption and / or vibration damping properties can be obtained. Unexpectedly, it has been found that when soft metal powder is used as the metal powder, high sound absorption and / or vibration damping properties that exceed those of vibration-damping rubber can be obtained.
[0050] By making the Brinell hardness of the finally obtained porous metal portion 10 or less, 5 or less, 3 or less, or 1 or less, extremely high sound absorption and / or vibration damping properties can be obtained.
[0051] The average particle size of the metal powder may be, for example, 10 μm or more, 50 μm or more, 100 μm or more, or 300 μm or more, or 2000 μm or less, 1500 μm or less, 1000 μm or less, 800 μm or less, 500 μm or less, or 300 μm or less, depending on the size of the pores in the finally obtained porous metal structure. For example, the average particle size of the metal powder may be 10 μm or more and 2000 μm or less, 50 μm or more and 1000 μm or less, or 100 μm or more and 500 μm or less.
[0052] The second composite may be in the form of mixed particles containing the first composite and a metal powder, or in the form of a slurry containing the first composite and a metal powder in a liquid medium. The liquid medium is not particularly limited as long as it can mix and / or knead the first composite and the metal powder relatively homogeneously, and may be, for example, an aqueous solvent such as water or alcohol, or an organic solvent such as toluene.
[0053] If the second composite is in the form of a slurry, the step of drying the liquid medium can be included prior to the step of sintering the metal powder. The drying step can be carried out at a temperature and for a time sufficient to remove the liquid medium, and can be carried out under reduced pressure.
[0054] The second composite may be in a phase-separated form in which the first composite is enveloped in the metal powder. In this case, the metal powder may envelope the first composite in the form of a slurry containing a liquid medium or the like. When the second composite is formed in such a form, the finally obtained porous metal structure having a bell structure can be in the form of particles.
[0055] When the second composite is produced in a form in which the first composite is wrapped with metal powder, thereby obtaining a porous metal structure having a bell structure in the form of particles, the average thickness of the layer of the wrapping metal powder may be 50 μm or more, 100 μm or more, 200 μm or more, 300 μm or more, 500 μm or more, 1 mm or more, 3 mm or more, or 5 mm or more, and may be 10 mm or less, 5 mm or less, 3 mm or less, 2 mm or less, 1.5 mm or less, 1 mm or less, 800 μm or less, or 500 μm or less. For example, the average thickness of the layer of the wrapping metal powder may be 50 μm or more and 10 mm or less, 100 μm or more and 5 mm or less, or 200 μm or more and 1 mm or less. This average thickness can be measured from the thickness of the porous part of the particle of the porous metal structure, and the thickness can be measured from an optical microscope photograph of a cross section passing through the substantial center part of the particle of the porous metal structure.
[0056] The shape of the second complex is not limited to a spherical or nearly spherical shape, but may be angular or the like.
[0057] <Step of sintering metal powder and step of removing shell-forming material> The manufacturing method of the present disclosure includes the steps of heating the second composite to sinter the metal powder and removing the shell-forming material from the second composite, which steps may be performed simultaneously or the step of sintering the metal powder may be performed followed by the step of removing the shell-forming material.
[0058] When a carbon-based shell-forming material is used as the shell-forming material, and a process for removing the carbon-based shell-forming material is carried out after the process for sintering the metal powder, it is preferable that the sintering of the metal powder is carried out under vacuum or in an inert atmosphere.
[0059] The sintering temperature and time in the step of sintering the metal powder can be appropriately selected according to the metal powder used, and are not particularly limited as long as the conditions are such that the porous metal portion serving as the base material of the porous metal structure can be appropriately formed. The sintering temperature may be 400°C or more, 500°C or more, 550°C or more, or 600°C or more, and 1500°C or less, 1000°C or less, 800°C or less, or 700°C or less. For example, the sintering temperature may be 400°C or more and 1500°C or less, or 500°C or more and 800°C or less. The sintering time may be 30 minutes or more, 1 hour or more, 2 hours or more, or 4 hours or more, and may be 12 hours or less, 10 hours or less, or 8 hours or less. For example, the sintering time may be 30 minutes or more and 12 hours or less, or 1 hour or more and 8 hours or less.
[0060] The step of removing the carbon-based shell-forming material is carried out in an oxygen-containing atmosphere. Oxygen is provided to the carbon-based shell-forming material of the first composite present inside through the continuous pores formed by sintering the metal powder in the second composite or through gaps in the unsintered metal powder. This allows the carbon-based shell-forming material to disappear as carbon dioxide in the heated second composite.
[0061] The oxygen-containing atmosphere is not particularly limited in terms of oxygen concentration, so long as it can cause the carbon-based shell-forming material to disappear as carbon dioxide, and may be an air atmosphere.
[0062] The heating temperature and time in the step of removing the carbon-based shell-forming material can be appropriately selected depending on the carbon-based shell-forming material used and the optional binder and / or coating material, which may or may not be carbonized. The heating temperature may be 300°C or more, 400°C or more, 500°C or more, 550°C or more, or 600°C or more, and 100°C or less, 800°C or less, 600°C or less, or 500°C or less. For example, the heating temperature may be 300°C or more and 1000°C or less, or 400°C or more and 800°C or less. The heating time may be 10 minutes or more, 30 minutes or more, 1 hour or more, or 2 hours or more, and may be 6 hours or less, 4 hours or less, or 3 hours or less. For example, the heating time may be 10 minutes or more and 6 hours or less, or 30 minutes or more and 4 hours or less.
[0063] When a liquid-soluble shell-forming material is used as the shell-forming material, if a step of removing the shell-forming material is performed after the step of sintering the metal powder, the liquid-soluble shell-forming material can be soluble in liquid after being heated to the sintering temperature of the metal powder or higher, and in this case, it is particularly preferable that the shell-forming material is a polymer that is soluble in an organic solvent. When the shell-forming material is dissolved in a liquid, dissolution can be promoted by performing a heat treatment, an ultrasonic treatment, or the like, as necessary.
[0064] As the solvent for dissolving the liquid-soluble shell-forming material, any well-known solvent can be appropriately selected depending on the type of shell-forming material used.
[0065] <<Method for manufacturing a metal structure having a bell structure>> The present disclosure further relates to a method for manufacturing a metal structure having a bell structure, including obtaining a plurality of porous metal structures having a bell structure, and impregnating the plurality of porous metal structures with molten metal and cooling.
[0066] The present inventors have found that such a method makes it possible to very easily manufacture a metal structure having a bell structure but including a solid metal portion. With such a method, a metal structure having a bell structure can be manufactured by a die casting method that is very advantageous for mass production, and the ratio of the solid metal portion and the bell structure can be appropriately selected, so that the balance between the vibration damping performance and the mechanical strength of the metal structure can be easily designed.
[0067] The metal structure obtained by this method has a bell structure and includes at least a non-porous portion, i.e., a solid portion, in a portion other than the porous portion around the bell structure. This allows the metal structure obtained by this method to have a higher mechanical strength than a structure substantially entirely composed of porous metal. Preferably, the metal structure obtained by this method includes a porous metal structure inside a solid metal portion, and more specifically, the metal structure has a sea-island structure including a porous metal structure as a plurality of domain portions and a solid metal portion as a matrix portion. Therefore, such a metal structure has a structure in which a porous metal portion is contained inside a solid metal portion, a shell is present in the porous metal portion, and inorganic particles are present in the shell in a movable manner.
[0068] <Step of Obtaining Multiple Porous Metal Structures> The process for obtaining a plurality of porous metal structures having a bell structure is not particularly limited as long as the porous metal structures have a bell structure. Therefore, a plurality of porous metal structures having a bell structure may be obtained by the methods described in Patent Documents 1 and 2 and other known methods, and a plurality of porous metal structures having a bell structure may be obtained by the above-mentioned manufacturing method of the present disclosure.
[0069] The porous metal structure having a bell structure may be molded and shaped into any shape, such as an amorphous shape; a spherical shape such as a perfect sphere or an oblong sphere; or a columnar shape such as a cylindrical shape or a rectangular column. For example, the porous metal structure having a bell structure may be manufactured using a molding machine. When a plurality of porous metal structures having a bell structure are obtained by the manufacturing method of the present disclosure, the step of sintering the metal powder and the step of removing the shell-forming material may be performed using a mold to obtain a porous metal structure shaped by the mold.
[0070] When a porous metal structure having a bell structure is used in the form of particles, a porous metal structure can be used in which a first composite is surrounded by metal powder to form a second composite. In such an embodiment, it is easy to manufacture a metal structure having an island-in-sea structure that includes the porous metal structure as a plurality of domain portions and includes a solid metal portion as a matrix portion, and such a metal structure is preferable because it can have high mechanical strength.
[0071] The average diameter of the particulate porous metal structure may be, for example, 0.5 mm or more, 1.0 mm or more, 3.0 mm or more, 5.0 mm or more, or 10 mm or more, or 100 mm or less, 50 mm or less, 30 mm or less, 20 mm or less, 10 mm or less, or 5.0 mm or less. For example, the average diameter of the porous metal structure may be 0.5 mm or more and 100 mm or less, or 1.0 mm or more and 10 mm or less. Here, the average diameter means the particle size at 50% of the cumulative value in the particle size distribution based on the number of randomly selected up to 100 porous metal structures measured along their major axes using a caliper.
[0072] <Step of Impregnating Porous Metal Structure with Molten Metal and Cooling> The method for producing a metal structure of the present disclosure further includes a step of impregnating a plurality of porous metal structures with molten metal and cooling the same. In this step, a plurality of the arbitrarily shaped porous metal structures obtained as described above are impregnated with molten metal and cooled, so that the molten metal forms a solid metal structure and the porous metal structure forms a porous portion around the bell structure. Since the molten metal does not penetrate to the deepest part of the continuous pores of the porous metal structure, the bell structure of the porous metal structure is included in the metal structure as it is.
[0073] This process may involve, for example, placing the plurality of porous metal structures in a mold containing molten metal and allowing the mold to cool, or may involve placing the solid metal and the plurality of porous metal structures in a mold and heating the mold to melt substantially only the solid metal.
[0074] When the solid metal is placed in a mold and heated to melt it, pressure may be applied as desired. The conditions for heating and / or pressing can be appropriately selected depending on the solid metal used, but are not particularly limited as long as the conditions can melt the solid metal.
[0075] The molten metal is not particularly limited, but may be, for example, a metal used in a die casting method. Examples of such metals include iron-based metals, copper-based metals, titanium-based metals, tungsten-based metals, aluminum-based metals, chromium-based metals, nickel-based metals, zinc-based metals, magnesium-based metals, tin-based metals, lead-based metals, and alloys of combinations thereof, and in particular, copper-based metals, aluminum-based metals, zinc-based metals, magnesium-based metals, tin-based metals, lead-based metals, and alloys of combinations thereof.
[0076] The volume fraction of the porous metal structure relative to the metal structure (porous metal structure / metal structure) may be 0.5 volume% or more, 1.0 volume% or more, 2.0 volume% or more, 3.0 volume% or more, 5.0 volume% or more, 10.0 volume% or more, 20.0 volume% or more, or 30.0 volume% or more, or 50.0 volume% or less, 30.0 volume% or less, 20.0 volume% or less, 10.0 volume% or less, or 5.0 volume% or less. This volume fraction can be, for example, 0.5 volume% or more and 50.0 volume% or less, or 1.0 volume% or more and 10.0 volume% or less. This volume fraction is calculated from the total volume of the porous metal structure actually used and the volume of the metal structure finally obtained.
[0077] <<Bell-structured porous metal structure>> The porous metal structure having a bell structure of the present disclosure may be obtained by the manufacturing method of a porous metal structure having a bell structure described above. Therefore, for each configuration of the porous metal structure having a bell structure of the present disclosure, reference can be made to each configuration described above regarding the manufacturing method of a porous metal structure having a bell structure of the present disclosure. Similarly, for the manufacturing method of the porous metal structure having a bell structure described above, reference can be made to each configuration related to the porous metal structure having a bell structure described below.
[0078] In the porous metal structure having a bell structure of the present disclosure, movable inorganic particles are present in a shell in a porous metal portion serving as a base material. The metal constituting the porous metal portion may be a metal formed from a metal powder that can be used in the above-mentioned method for producing a porous metal structure, and the inorganic particles may be inorganic particles that can be used in the above-mentioned method for producing a porous metal structure.
[0079] In one embodiment, the porous metal structure having a bell structure of the present disclosure has inorganic particles having a very high specific gravity, for example, 6.0 g / cm 3 or more than 7.0g / cm 3 It has a specific gravity of more than 100%.
[0080] The present inventors have found that when inorganic particles having such a specific gravity are used, the bell-shaped porous metal structure has very high sound absorption and / or vibration damping properties. Examples of such inorganic particles include iron, copper, tungsten, and alloys and compounds thereof. The porous metal portion that serves as the base material in such a porous metal structure can be made of the metal of the metal powder mentioned in the above-mentioned manufacturing method, and can be made of an aluminum-based metal in particular.
[0081] When the shell-forming material is finally removed to obtain a porous metal structure, the average particle size of the inorganic particles is as described above in the method for producing a porous metal structure. When the shell-forming material is left in the porous metal structure to obtain a porous metal structure as it is as a shell, the sizes of the shell-forming material and the inorganic particles are as described above in the method for producing a porous metal structure.
[0082] The average diameter of the shell of the bell structure of the porous metal structure of the present disclosure may be 50 μm or more, 100 μm or more, 300 μm or more, 500 μm or more, 700 μm or more, 1000 μm or more, or 1500 μm or more, or 10000 μm or less, 8000 μm or less, 5000 μm or less, 3000 μm or less, 2000 μm or less, 1500 μm or less, 1000 μm or less, 800 μm or less, or 500 μm or less. For example, the average diameter of the shell may be 50 μm or more and 10000 μm or less, 300 μm or more and 3000 μm or less, or 500 μm or more and 1500 μm or less. In this specification, the average diameter of the shell means the particle size at 50% of the cumulative value in the particle size distribution based on the number of randomly selected up to 100 shells measured on the cut surface of the porous metal structure or the metal structure using an optical microscope (or a vernier caliper if the diameter is large). As shown in FIG. 3, the outline of the shell (2) is not necessarily clear, so a person skilled in the art will determine the outline of the shell (2) within an appropriate range and then determine the long axis of the shell. Note that, in the case where the measured values in the present disclosure vary depending on the cut surface, the measured values will be obtained from multiple arbitrarily selected cut surfaces and averaged.
[0083] The average diameter of the shell may be 1.5 times or more, 2.0 times or more, 3.0 times or more, 4.0 times or more, 5.0 times or more, or 20.0 times or less, 10.0 times or less, 8.0 times or less, 6.0 times or less, 5.0 times or less, or 3.0 times or less. The average diameter of the shell may be in the range of 1.5 times or more and 20.0 times or less, or 2.0 times or less and 10.0 times or less, of the average particle size of the inorganic particles.
[0084] In one embodiment, the porous metal structure having a bell structure of the present disclosure has an average particle size of the inorganic particles ranging from 100 μm to 5000 μm, and an average diameter of the shells ranging from 1.5 to 10.0 times the average particle size of the inorganic particles; an average particle size of the inorganic particles ranging from 100 μm to 1000 μm, and an average diameter of the shells ranging from 2.0 to 5.0 times the average particle size of the inorganic particles.
[0085] The bell structure of the porous metal structure of the present disclosure may have a ratio of the particle diameter of the inorganic particles to the diameter of the shell (particle diameter of the inorganic particles / diameter of the shell) of 0.1 or more, 0.2, 0.3 or more, or 0.5 or more, and may be 0.8 or less, 0.6 or less, 0.4 or less, or 0.2 or less. For example, this ratio may be 0.1 or more and 0.8 or less, or 0.2 or more and 0.6 or less. It is not necessary that all of the bell structures of the porous metal structure of the present disclosure are in the above range, and the bell structures of the porous metal structure of the present disclosure that fall within the above ratio range may be 10% or more, 20% or more, 30% or more, 50% or more, or 80% or more, and may be 95% or less, 90% or less, 85% or less, 80% or less, or 70% or less, on a number basis. In this specification, particle diameter and diameter refer to diameters measured using an optical microscope (or a caliper if the diameter is large).
[0086] The volume fraction of the bell structure of the porous metal structure of the present disclosure may be 0.5 volume% or more, 1.0 volume% or more, 2.0 volume% or more, 3.0 volume% or more, 5.0 volume% or more, 10.0 volume% or more, 15.0 volume% or more, or 20.0 volume% or more, or 30.0 volume% or less, 20.0 volume% or less, 15.0 volume% or less, 10.0 volume% or less, or 5.0 volume% or less, calculated using the number of shells per unit area of the cut surface of the structure, the unit volume of the structure calculated from the unit area, and the volume of the shells assumed to be spherical calculated from the average diameter of the shells. This volume fraction may be, for example, 0.5 volume% or more to 30.0 volume% or less, or 1.0 volume% or more to 15.0 volume% or less.
[0087] When the average diameter of the shell and the average particle size of the inorganic particles are within such ranges, when the final porous metal structure is subjected to vibration, the inorganic particles are likely to collide with the wall surface of the shell in the bell structure, resulting in extremely high vibration damping properties, which is preferable.
[0088] The bell-structured porous metal structure of the present disclosure is preferably a combination of the above-mentioned embodiments. That is, the bell-structured porous metal structure of the present disclosure has an inorganic particle density of 6.0 g / cm. 3 or more than 7.0g / cm 3 It is preferable that the inorganic particles have a specific gravity of 100 μm or more and 5000 μm or less, and that the average diameter of the shell is in the range of 1.5 times or more and 10.0 times or less the average diameter of the inorganic particles. For the preferable numerical ranges, the above description can be referred to.
[0089] When the porous metal structure having a bell structure is in the form of particles, its average diameter is as described for the process for obtaining a plurality of porous metal structures, and the thickness of the porous portion is as described for the average thickness of the layer of the enveloping metal powder when the second composite is produced in the form in which the first composite is enveloped with metal powder. When the porous metal structure having a bell structure is in the form of particles, it has been found that when the average diameter and the thickness of the porous portion are in the above-mentioned ranges, when a metal structure is produced using this, molten metal is less likely to penetrate into the shell, and the bell structure is maintained.
[0090] <Metal structure with bell structure> The metal structure having a bell structure of the present disclosure may be obtained by the above-mentioned method for manufacturing a metal structure having a bell structure. Therefore, for each configuration of the metal structure having a bell structure of the present disclosure, reference can be made to each configuration described above regarding the method for manufacturing a metal structure having a bell structure of the present disclosure. Similarly, for the method for manufacturing a metal structure having a bell structure, reference can be made to each configuration of the metal structure having a bell structure described below.
[0091] The metal structure having a bell structure of the present disclosure includes a porous metal structure having a bell structure as described above inside a solid metal portion. Preferably, the metal structure having a bell structure of the present disclosure has a sea-island structure including a porous metal structure having a bell structure as a plurality of domain portions and a solid metal portion as a matrix portion.
[0092] The average diameter of the porous metal structure having a bell structure contained in the metal structure of the present disclosure may be, for example, 0.5 mm or more, 1.0 mm or more, 3.0 mm or more, 5.0 mm or more, or 10 mm or more, and may be 100 mm or less, 50 mm or less, 30 mm or less, 20 mm or less, 10 mm or less, or 5.0 mm or less. For example, the average diameter of the porous metal structure having a bell structure may be 0.5 mm or more and 100 mm or less, or 1.0 mm or more and 10 mm or less. In this specification, the average diameter of the porous metal structure having a bell structure contained in the metal structure means the particle size at 50% of the cumulative value in the particle size distribution based on the number of the porous metal structures, which is measured by measuring the major axis of up to 100 randomly selected porous metal structures on the cut surface of the metal structure using an optical microscope (or a vernier caliper if the diameter is large). As shown in FIG. 11, the outline of the porous metal structure is not necessarily clear, so a person skilled in the art will determine the major axis of the shell after defining the outline of the shell within an appropriate range.
[0093] The volume fraction of the porous metal structure having a bell structure relative to the metal structure (porous metal structure having a bell structure / metal structure) may be 0.5 volume% or more, 1.0 volume% or more, 2.0 volume% or more, 3.0 volume% or more, 5.0 volume% or more, 10.0 volume% or more, 20.0 volume% or more, or 30.0 volume% or more, or 50.0 volume% or less, 30.0 volume% or less, 20.0 volume% or less, 10.0 volume% or less, or 5.0 volume% or less, calculated using the number of porous metal structures per unit area of the cut surface of the metal structure, the unit volume of the metal structure calculated from the unit area, and the volume of the porous metal structure assumed to be spherical calculated from the average diameter of the porous metal structure. This volume fraction may be, for example, 0.5 volume% or more and 50.0 volume% or less, or 1.0 volume% or more and 10.0 volume% or less.
[0094] The porous metal structure having a bell structure and the metal structure having a bell structure of the present disclosure are used in various applications by taking advantage of their excellent sound absorption, sound insulation, vibration damping and mechanical strength. For example, they are preferably used for automobile parts, structural materials and soundproofing materials, aircraft parts, structural materials and soundproofing materials, train parts, structural materials and soundproofing materials, home appliance parts, structural materials and soundproofing materials for home appliance housings, structural materials and soundproofing materials for exterior walls of buildings, structural materials and soundproofing materials for lining materials, structural materials and soundproofing materials for roofing materials, materials for civil engineering and construction machinery, or structural materials and soundproofing materials for soundproof walls on highways and railway lines. Among these, they are particularly suitable for automobile parts.
[0095] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto. EXAMPLES
[0096] Experiment 1. Model experiment on vibration absorption using a bell structure We built a model and conducted experiments to examine how the bell structure absorbs vibrations.
[0097] Figure 1 shows a schematic diagram and experimental results of how the internal particles move when vibration is applied to a structure having a bell structure with a spherical shell of 1.0 mm diameter, in which zirconia particles of 0.2 mm to 0.6 mm diameter are used as the internal particles. Specifically, Figure 1 shows by color the state in which the internal particles are in accordance with the frequency and amplitude of the applied vibration, that is, one of five states from "a. stationary state" to "e. collision motion".
[0098] As shown in Figure 1, regardless of the diameter and vibration amplitude of the internal particles, the internal particles were in a "static state" up to about 10 Hz. When the vibration frequency was increased from about 10 Hz, the internal particles started to move back and forth within the shell, then changed to a state of "c. wall-moving motion" where the internal particles climbed the wall and moved away. When the vibration frequency was further increased, the internal particles continued to rotate within the wall, changing to a "continuous rotational motion" state. In these motion states b to d, the vibration was absorbed by friction between the internal particles and the wall. When the diameter of the zirconia particles was 0.4 mm and 0.6 mm, the internal particles changed to "e. collision motion" where the internal particles collided with the wall within a certain range of amplitude and frequency. Surprisingly, in state e, where the internal particles collided with the wall of the shell, the internal particles made frictional motion within the shell, and the vibration damping was found to be increased by one to two orders of magnitude compared to states b to d.
[0099] Therefore, it was found that when the internal particles do not move much due to reasons such as the vibrations received by the porous metal structure being very small, the vibration damping properties are low, when the internal particles move within the shell, the vibration damping properties are relatively high, and when the internal particles collide with the wall surface of the shell, the vibration damping properties are extremely high.
[0100] Experiment 2: Comparison experiment between porous metal structures with bell structure and other metal structures <Production Example> A porous metal structure with a bell structure was fabricated as shown diagrammatically in FIG.
[0101] In the first step, the carbon-based shell-forming material and inorganic particles were bound with a binder to form a first composite. Specifically, 1 gram of granulated sugar (Nissin Sugar Co., Ltd.) was heated and dissolved as a binder. In addition, 0.8 grams (3 volume %), 1.6 grams (6 volume %), and 2.4 grams (9 volume %) of spherical zirconia particles (average particle size 400 μm, Nikkato Co., Ltd.) were dispersed as inorganic particles in the molten liquid in which the binder was dissolved. 6 grams of powdered activated carbon (30 μm, U.S.A. Co., Ltd.) was added as a carbon-based shell-forming material and stirred. In this way, a first composite in which activated carbon was attached to the surface of the zirconia particles was formed.
[0102] In the second step, the first complex was coated with a coating material. Specifically, the first complex was taken out of the binder melt, and a coating material (Bodypen, Soft99 Corporation) containing an acrylic resin, a black pigment, and an organic solvent was sprayed onto the first complex to coat the first complex. However, the solid weight of the coating material was much smaller than the sugar contained in the first complex.
[0103] As the third step, classification was performed. Specifically, classification was performed by sieving, and the first complexes having a major axis x of about 700 μm to 1200 μm were collected.
[0104] In the fourth step, the first composite and the metal powder were mixed with a liquid medium to obtain a second composite. Specifically, 0.3 to 0.9 grams of ethanol, the first composite (0.8 grams (3 volume %), 1.6 grams (6 volume %), and 2.4 grams (9 volume %), respectively), and Al powder (average particle size 150 μm, melting point 660° C., Hikari Material Industry Co., Ltd.) (5.6 grams (3 volume %), 4.8 grams (6 volume %), and 4.0 grams (9 volume %) as metal powder, and 1.6 grams of Al-12Si powder (average particle size 150 μm, melting point 577° C., Hikari Material Industry Co., Ltd.) were added and mixed to obtain a second composite in the form of a slurry. Here, the volume % was calculated from the volume and number of the first composite actually used and the volume of the porous metal structure finally obtained.
[0105] In the fifth step, the liquid medium was removed from the second composite by drying. Specifically, the second composite in the form of a slurry was placed in a graphite jig having a rectangular parallelepiped groove, covered with a lid and placed with a weight, and then heated at 100° C. for 30 minutes to remove the ethanol by drying.
[0106] In the sixth step, the binder contained in the second composite was carbonized. Specifically, the second composite was placed in a groove of the jig with a lid on and heated at 400°C for 1 hour in a nitrogen atmosphere to carbonize the sugar binder and a small amount of coating material.
[0107] In the seventh step, the metal powder of the second composite was sintered. Specifically, the second composite that had been subjected to the sixth step was heated in a vacuum at 600° C. for two hours.
[0108] In the eighth step, the carbon-based shell-forming material contained in the second composite was removed. Specifically, the second composite in which the metal powder had been sintered in the seventh step was removed from the graphite jig and heated in air at 470°C for 1 hour.
[0109] As a result, a porous metal structure of Example 1 (Ex.1) was obtained in which the porous metal portion was composed of an aluminum-based metal and contained zirconia particles as movable internal particles and had a bell structure in various amounts.
[0110] Preparation of Comparative Structures Based on the above manufacturing method, a porous metal structure containing zirconia particles but no shell is formed and the zirconia particles are fixed to the porous metal part (Comparative Example 1, C.Ex.1); a porous metal structure containing a shell but no zirconia particles (Comparative Example 2, C.Ex.2); a porous metal structure consisting only of a porous metal part having neither internal particles nor shell (Comparative Example 3, C.Ex.3); and a solid metal structure (Comparative Example 4, C.Ex.4) were prepared, and their vibration damping performance was compared. Note that the metal parts of all the examples were made of aluminum-based metals of almost the same composition.
[0111] Observation results from SEM photographs 3 shows SEM photographs of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, which contain 6 volume % bell structures. It can be seen that in Example 1, a shell (2) is formed in the porous metal portion (3), and movable internal particles (1) exist inside the shell. On the other hand, it can be seen that in Comparative Example 1, the internal particles are not movable, in Comparative Example 2, a shell exists but no internal particles exist, and in Comparative Example 3, neither a shell nor internal particles exist.
[0112] <Evaluation of vibration control performance> The vibration damping characteristics were measured using a vibration damping characteristic tester that was made in-house with reference to the Japanese Industrial Standards (JIS G0602-1993). Specifically, the vibration damping characteristics were evaluated by the central excitation method. The random signal generated by the FFT analyzer was amplified by a power amplifier and sent to the vibrator, and random vibration was applied to the test piece. The acceleration a(t) and load f(t) of the vibration applied by the impedance head attached to the bottom of the test piece were detected in the form of voltage. The detected voltage was amplified by a charge amplifier, and then a fast Fourier transform was performed by the FFT analyzer. The acceleration was frequency integrated to calculate the velocity V(f) and mechanical impedance (F(f) / V(f)). The loss factor was measured by the half-width method from the vicinity of the anti-resonance point. The test piece (Sample) was prepared by bonding an aluminum substrate (j) to the bottom of the fabricated metal structure (i) using an epoxy adhesive. Figure 4 shows a schematic diagram of the evaluation device and test piece.
[0113] <result> The evaluation results are shown in Fig. 5. As can be seen from these results, the porous metal structure having a bell structure of Example 1 according to the present disclosure has extremely high vibration-damping performance. In particular, in a comparison between Example 1 and Comparative Example 3, the loss factor η differs by approximately 19 times between Example 1 (η = 0.03129 at 293 Hz) and Comparative Example 3 (η = 0.00161 at 512 Hz), demonstrating that extremely high vibration-damping performance can be obtained.
[0114] Experiment 3: Experiment with changing the internal particles of the bell structure A porous metal structure having a bell structure was obtained at 6 volume % in the same manner as in Experiment 2 above, except that the zirconia particles were changed to copper particles (average particle size 400 μm, Hikari Materials Industry Co., Ltd.), iron particles (average particle size 400 μm, IKK Shot Co., Ltd.), and glass particles (average particle size 400 μm, AS ONE Corporation).
[0115] The vibration-damping performance was evaluated in the same manner as in Experiment 2. The evaluation results are shown in FIG. 6. It was found that the vibration-damping performance improved as the specific gravity of the internal particles increased, for example, glass (Glass), zirconia (Zr), iron (Fe), and copper (Cu). In particular, it was found that when copper particles were used (η=0.06386 at 205 Hz), approximately 40 times the vibration-damping performance was obtained compared to Comparative Example 3 in Experiment 2 (η=0.00161 at 512 Hz). It was also found that when copper particles were used, approximately half the vibration-damping performance was obtained compared to vibration-damping rubber (Rubber, Naigai Rubber Co., Ltd., product name Hanenite).
[0116] Experiment 4. Experiment with changing the amount of bell structure A porous metal structure having a bell structure was obtained in the same manner as in Experiment 2 above, except that the zirconia particles were changed to copper particles (average particle size 400 μm, Hikari Materials Industry Co., Ltd.).
[0117] The vibration-damping performance of these was evaluated in the same manner as in Experiment 2. The evaluation results are shown in Figure 7. It was found that the vibration-damping performance improved by increasing the amount of the bell structure. In particular, when the first composite was manufactured so that it was 9 volume % (η = 0.11275 at 223 Hz), it was found that vibration-damping performance was approximately 70 times higher than that of Comparative Example 3 in Experiment 2 (η = 0.00161 at 512 Hz). Surprisingly, it was also found that in this case, vibration-damping performance comparable to that of vibration-damping rubber (Naigai Rubber Co., Ltd., product name Hanenite) was obtained.
[0118] Experiment 5. Example of manufacturing a metal structure with a bell structure A metal structure having a bell structure was fabricated as shown diagrammatically in FIG.
[0119] In the first step, a first composite having activated carbon attached to the surfaces of metal particles was obtained in the same manner as in the first to third steps of Experiment 2 above.
[0120] In the third step, 6 grams of Al powder (average particle size 150 μm, melting point 660°C, Hikari Materials Industry Co., Ltd.) and 4 grams of Al-12Si powder (average particle size 150 μm, melting point 577°C, Hikari Materials Industry Co., Ltd.) were kneaded in ethanol to form a slurry.
[0121] In the fourth step, the slurry obtained in the third step was poured into each hole of a graphite jig having a shape of a takoyaki maker, that is, two graphite jigs having a plurality of hemispherical holes.
[0122] In the fifth step, the first composites obtained in the second step were poured one by one into the holes into which the slurry had been poured in the fourth step to form second composites.
[0123] In the sixth step, the two jigs were combined or one of the jigs was removed, and the ethanol was dried, the binder was carbonized, the metal powder was sintered in a vacuum at 580° C. for 2 hours, and the carbon-based shell-forming material was removed in an electric furnace in air at 470° C. in the same manner as in Experiment 2. As a result, a plurality of spherical porous metal structure particles with a diameter of about 3 mm were produced.
[0124] As shown in Fig. 9(a), the porous metal structure particle (10) thus obtained has, at the stage of the fifth step, Al alloy grains (3) which are metal powder present at the outermost part, metal balls (1) which are inorganic particles present at the center, and a carbon-based shell-forming material (2a) and binder (2b) present between the metal powder and the inorganic particles. By going through the sixth step, as shown in Fig. 9(b), the carbon-based shell-forming material and binder disappear, and a cavity (shell, 2) is generated in the sintered metal powder particle, where the inorganic particles (1) can exist in a movable state.
[0125] In the seventh step, 11 grams of white metal (SnSbCu alloy) was placed in the bottom of the graphite jig as the metal to be melted, and 109 of the spherical porous metal structures were placed on top of the white metal. While applying pressure from above, the jig was heated at 400°C for 6 minutes in an electric furnace in a nitrogen atmosphere to prevent the graphite jig from burning. This caused the white metal to melt and be impregnated between the spherical porous metal structures. Finally, the jig was removed from the electric furnace and cooled.
[0126] The appearance and cross-sectional photograph of the spherical porous metal structure taken with an optical microscope are shown in Figure 10. The cross-sectional photograph was taken after embedding the spherical porous metal structure in resin and polishing the cross-section.
[0127] FIG. 11 shows a cross-sectional photograph of the finally obtained metal structure having a bell structure taken by an optical microscope and an enlarged cross-sectional photograph taken by an SEM.
[0128] As is clear from this photograph, a metal structure having a bell structure was obtained, which contains a porous metal portion (10) having a bell structure as a plurality of domain portions and a solid metal portion (20) as a matrix portion. Surprisingly, it was found that the molten metal (20) did not penetrate into the inside of the bell structure of the porous metal structure (10), and the porous metal structure (10) having a bell structure was directly included in the metal structure as a domain portion.
[0129] It was found that this metal structure has a solid metal portion that provides high mechanical strength, and a porous metal portion having a bell structure that provides high vibration damping performance.
[0130] Experiment 6. Experiment on a porous metal structure with a bell structure when the shell-forming material becomes the shell itself <Production Example> To obtain inorganic particles, a copper wire was prepared. As shown in FIG. 12, in the first step, the copper wire was cut to a length of 1.5 mm or 0.75 mm. In the second step, the cut copper wire was placed in an aluminum pipe. In the third step, the aluminum pipe was cut to a width of 2.5 mm, thereby blocking the ends, and a first composite was obtained.
[0131] Thereafter, the same steps as those from the fourth step onwards in Experiment 2 were carried out so that the first composite was 3 volume % to obtain a porous metal structure having a bell structure. A cross section of the bell structure of the finally obtained porous metal structure is shown in Fig. 13. Fig. 13(a) is a cross section of a bell structure containing inorganic particles with a long axis length of 1.5 mm, and Fig. 13(b) is a cross section of a bell structure containing inorganic particles with a long axis length of 0.75 mm.
[0132] The vibration damping performance of these was evaluated in the same manner as in Experiment 2. The evaluation results are shown in Fig. 14, in comparison with the results of a structure produced in Experiment 4 so that the first composite containing copper particles was 3 volume %.
[0133] As shown in Figure 14, the porous metal structure with a cylindrical bell structure has high vibration-damping performance, and in particular, the bell structure (1.5 mm) containing inorganic particles with a long axis length of 1.5 mm had extremely high vibration-damping performance. It was also found that the bell structure (0.75 mm) containing inorganic particles with a long axis length of 0.75 mm had higher vibration-damping performance than the spherical bell structure (Sphere) in the high frequency range.
[0134] Experiment 7. Experiment on porous metal structure using soft metal powder A porous metal structure was produced using Sn (tin) powder (average particle size 150 μm or less, Kojundo Chemical Laboratory Co., Ltd.) instead of or in addition to the Al powder (average particle size 150 μm, melting point 660°C, Hikari Materials Industry Co., Ltd.) used to obtain the second composite.
[0135] FIG. 15 shows the relationship between the Brinell hardness (HBW) of the obtained porous metal and the mass ratio of the Sn powder to the total metal powder.
[0136] The results of the vibration damping performance when all the metal powder was Sn powder (Sn ratio = 1.00), when 67 mass % of the metal powder was Sn powder (Sn ratio = 0.67), and when 50 mass % of the metal powder was Sn powder (Sn ratio = 0.50) are shown in Fig. 16. Note that here, similarly to the production in Experiment 2, each porous metal structure was produced by adjusting the first composite containing zirconia particles to 6 volume %.
[0137] As shown in FIG. 16, it was found that the higher the ratio of Sn powder in the metal powder, the higher the vibration damping performance. [Explanation of symbols]
[0138] a FFT Analyzer b. Power amplifier c vibrator d Impedance Head e Charge amplifier f Computer g Stereo Microscope h Display i Metal structure j Al base material 1 internal particle 2. Shell (hole) 2a Carbon-based shell forming material 2b Binder 3 Porous metal part 10 Porous metal structure 20 Solid metal parts
Claims
1. Obtaining a first composite of inorganic particles and a shell-forming material; Obtaining a second composite of the first composite and a metal powder; heating the second composite body to sinter the metal powder; and removing the shell-forming material from the second composite body to form a bell-shaped structure having the sintered metal powder as the shell and the inorganic particles as the inner particles; A method for producing a porous metal structure having a bell structure, comprising:
2. The method according to claim 1 , further comprising the step of adding a binder for binding the inorganic particles and the shell-forming material when obtaining the first composite body.
3. 3. The manufacturing method according to claim 1, wherein the shell-forming material is a carbon-based shell-forming material, and the second composite is heated in an oxygen-containing atmosphere to remove the carbon-based shell-forming material from the second composite.
4. The method according to claim 1 , wherein the shell-forming material is a liquid-soluble shell-forming material, and the liquid-soluble shell-forming material is removed from the second complex by dissolving it in a liquid.
5. Obtaining a first composite of inorganic particles and a shell-forming material; Obtaining a second composite of the first composite and a metal powder; heating the second composite body to sinter the metal powder; and The shell-forming material is used as the shell and the inorganic particles are used as inner particles to form a bell-shaped structure. A method for producing a porous metal structure having a bell structure, comprising:
6. The method according to claim 5 , wherein the shell-forming material is cylindrical.
7. The inorganic particles have a density of 7.0 g / cm 3 The method according to any one of claims 1 to 6, wherein the metal powder is an aluminum-based metal powder, a tin-based metal powder, or a combination thereof.
8. The method according to any one of claims 1 to 7, wherein the porous metal structure is obtained in the form of particles by enveloping the first composite with the metal powder to obtain a second composite.
9. Obtaining a plurality of porous metal structures having a bell-shaped structure by the manufacturing method according to any one of claims 1 to 8; and impregnating the plurality of porous metal structures with molten metal and cooling; A method for producing a metal structure having a bell structure, comprising:
10. A porous metal structure having a bell structure in which movable inorganic particles are present in a shell, the inorganic particles having an average particle size of 100 μm or more and 5000 μm or less, and the shell having an average diameter in the range of 1.5 to 10.0 times the average particle size of the inorganic particles (excluding those in which hollow silica particles and their residues remain inside the shell).
11. The porous metal structure having a bell structure according to claim 10 , wherein the shell is cylindrical.
12. 12. The porous metal structure of claim 10 or 11, wherein the porous metal structure comprises tin.
13. The porous metal structure according to any one of claims 10 to 12, in the form of particles.
14. A metal structure comprising the porous metal structure according to any one of claims 10 to 13 inside a solid metal part.
15. The metal structure according to claim 14, having an islands-in-a-sea structure, comprising the porous metal structure as a plurality of domain portions and the solid metal portion as a matrix portion.
Citation Information
Patent Citations
Bell-structured particle and method for producing the same
JP2011001258A
Porous sintered body
JP2013004367A
Perfume composition
JP2014005459A
Method for manufacturing metal structure
JP2020070482A